Multiculturalismo na educação: evidências na formação docente - Canassa, Júlia Maria Bertin [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present work seeks to establish the importance of multiculturalism as a field of discussion in the Brazilian educational context, bringing first the various concepts of the term multiculturalism and then, in the context of teacher education, based on articles by Brazilian authors such as Candau, Moreira, Canen and others and other authors who have produced literature dealing with multiculturalism, multi/intercultural education and its implications for everyday school life, didactics, human rights education, the curriculum and its practices, and teacher training. This bibliographical research (GIL, 2002) was based on an analysis of articles selected in the Google Scholar of the three aforementioned authors, references in the subject, in the period 2008-2017; Through this work, the general objective was to understand the perspectives of pedagogical work attentive to multiculturalism and, as specific objectives, to differentiate the concept of multiculturalism from different theoretical perspectives, systematizing and analyzing the scientific production that deals with initial teacher training under a critical multicultural perspective. So that we can effectively work on the plurality that underlies our society, therefore, it’s necessary to invest in teacher training for the numerous specificities in relation to the processes, times and forms of student learning, taking into account the importance of the student's role in the preparation of curriculums of our education.

O presente trabalho buscou estabelecer a importância do multiculturalismo como campo de discussão no contexto educacional brasileiro, trazendo primeiramente os diversos conceitos do termo multiculturalismo e, posteriormente, no âmbito da formação docente, a partir de artigos de autores brasileiros como Candau, Moreira, Canen e de outros autores que produziram literaturas que tratam do multiculturalismo, da educação multi/intercultural e suas implicações para o cotidiano escolar, a didática, a educação nos direitos humanos, o currículo e suas práticas e a formação de professores. A presente pesquisa, de caráter bibliográfico (GIL, 2002) foi feita com base em uma análise de artigos selecionados no Google Scholar dos três autores acima citados, referências no assunto, no período de 2008-2017. Através deste trabalho, pretendeu-se como objetivo geral compreender as perspectivas de trabalho pedagógico atentas ao multiculturalismo e, como objetivos específicos, diferenciar o conceito de multiculturalismo de diferentes perspectivas teóricas, sistematizando e analisando a produção científica que trata da formação inicial de professores sob uma perspectiva multicultural crítica. Para que possamos efetivamente trabalharmos a pluralidade que embasa nossa sociedade, portanto, é preciso um investimento na formação docente para as inúmeras especificidades em relação aos processos, tempos e formas de aprendizagens dos alunos, levando em consideração a importância do protagonismo do aluno na elaboração dos currículos de nossa educação.
Multiculturalism in education: evidence in training teacher
Keywords: Multiculturalism; Diversity; Plurality; Education; Teacher training; Curriculum; Multiculturalismo; Diversidade; Pluralidade; Formação docente; Currículo